Professional Property Estimation in Lithuania: Reference Points - Galinienė, Birutė (Ekonomika, 1997)
The original development of the national property market requires the professional estimation of properly based on many years’ experience of other countries, on the requirements of international property estimation standards, and OD legal regulations and government resolutions passed in Lithuania. The improvement of professional activity of property estimators requires the preparation of a qualification training system for professional estimators of property. This should be a training started in higher academic schools along with periodically organised long-term theoretical instruction courses, traineeships, etc., throughout the whole period of professional activity. It is necessary to prepare a system of professional qualification standards (classes) and requirements for estimators of property. The creation and realisation of a professional property estimation system is inseparable from the system of professional responsibility of property estimators (settling of disputes between two interested parties) and the preparation of professional identity insurance programs.